PERANAN GAYA HIDUP DAN PENDAPATAN TERHADAP KEPUTUSAN PEMBELIAN STARBUCKS COFFEE DI CENTER POINT MEDAN - Simangunsong, Ridhon MB.; Manalu, Darma; Roshinta, Johanna (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to determine how the role of lifestyle and income on the decision to purchase StarbucksCoffee at Center Point Medan, either partially or simultaneously. This study uses a descriptivequalitative approach to show how lifestyle and income play a role in purchasing Starbucks Coffee atCenter Point Medan. In this research. The population in this research is all Starbucks Coffee CenterPoint buyers whose exact number is not known. Sampling using the Lemeshow formula amounted to 96people. Data collection was carried out using a questionnaire. The results of this study indicate thatthere is a very large role and is positive and significant in lifestyle variables on purchasing decisionsfor Starbucks Coffee at Center Point Medan. It is suggested that Starbucks Center Point Medan shouldcontinue to maintain the quality of coffee that is already well-known and the facilities are goodaccording to the lifestyle and income of Starbucks customers